Correction factors for ionization chamber measurements with the 'Valencia' and 'large field Valencia' brachytherapy applicators. (8th June 2018) - Gimenez-Alventosa, V; Gimenez, V; Ballester, F; Vijande, J; Andreo, P
Abstract: Treatment of small skin lesions using HDR brachytherapy applicators is a widely used technique. The shielded applicators currently available in clinical practice are based on a tungsten-alloy cup that collimates the source-emitted radiation into a small region, hence protecting nearby tissues. The goal of this manuscript is to evaluate the correction factors required for dose measurements with a plane-parallel ionization chamber typically used in clinical brachytherapy for the 'Valencia' and 'large field Valencia' shielded applicators. Monte Carlo simulations have been performed using the PENELOPE-2014 system to determine the absorbed dose deposited in a water phantom and in the chamber active volume with a Type A uncertainty of the order of 0.1%. The average energies of the photon spectra arriving at the surface of the water phantom differ by approximately 10%, being 384 keV for the 'Valencia' and 343 keV for the 'large field Valencia'. The ionization chamber correction factors have been obtained for both applicators using three methods, their values depending on the applicator being considered. Using a depth-independent global chamber perturbation correction factor and no shift of the effective point of measurement yields depth-dose differences of up to 1% for the 'Valencia' applicator. Calculations using a depth-dependent global perturbation factor, or a shift of the effective point of measurement combined with a constant partial perturbation factor, result in differences of about 0.1% for both applicators. The results emphasize the relevance of carrying out detailed Monte Carlo studies for each shielded brachytherapy applicator and ionization chamber.